THE CORRELATION BETWEEN STUDENTS' VOCABULARY MASTERY AND THEIR ENGLISH LEARNING ACHIEVEMENT AT SMP NEGERI 2 KOTA TERNATE - Isma Arif; Sutaryo Sutaryo; Sri Ayu Budi Lestari (Cakrawala Bahasa, 2023)
The objective of this research to know the correlation between students’ vocabulary mastery and their English learning achievement at SMP Negeri 2 Kota Ternate. Data ware collected by through tests. A sample of 30 students of class VIII6 were selected purposively. The results of this research indicate that the average score of the students' vocabulary mastery test was moderate (56.86) and the score of the students' English achievement was also moderate (57). The test value of the correlation between the variables X and Y (correlated) was found a very high and r count result (0.9233) exceeded the t-table value (0.361) at a significant level of 5%. Thus the alternative hypothesis (Hi) is accepted and the hypothesis (Ho) is rejected. It can be concluded that the students’ vocabulary mastery was highly and significant correlated with the students’ English learning achievement.